Evaluation of Bacillus subtilis ATCC PTA-122264 on the fecal characteristics and microbiota of healthy adult dogs subjected to an abrupt diet change - Oba, Patrícia M.; Swanson, Olivia R.; Kang, Yifei; Mioto, Julio C.; Menton, John F.; Vinay, Elena; Millette, Mathieu; Kelly, Melissa R.; Swanson, Kelly S. (Frontiers in Veterinary Science, 2025)
Abrupt dietary transitions are common in pets, but can lead to digestive disturbances, altered gut microbiota composition, and impaired intestinal integrity. The consumption of live microorganisms may have potential to mitigate these effects by stabilizing the gut microbiota and enhancing intestinal functionality. The current study aimed to evaluate the effects of Bacillus subtilis ATCC PTA-122264 supplementation on fecal characteristics, microbiota composition, and dysbiosis index of dogs undergoing an abrupt dietary change. Twelve healthy adult spayed female beagle dogs (6.0 ± 1.14 yr; 8.7 ± 0.91 kg body weight) were used in a replicated 3 × 3 Latin square design. In each experimental period, dogs were allotted to one of three treatments and fed a high-fiber kibble diet for 28 d: (1) 250 mg/d of maltodextrin (control), (2) 1 × 109 colony-forming units (CFU)/d of B. subtilis, or (3) 5 × 109 CFU/d of B. subtilis. All dogs were then abruptly transitioned to a high-protein, high-fat canned diet and fed for 14 d. Fresh fecal samples were collected before (d 0) and 2, 6, 10, and 14 d after the diet change for fecal scoring, pH, dry matter (DM) content, and microbiota analysis. Data were statistically analyzed to identify differences due to treatment, time, and treatment*time interactions, with p < 0.05 accepted as being significant. Diet change did not impact fecal pH or scores but reduced fecal DM percentage and bacterial alpha diversity measures. Bacterial beta diversity analysis revealed a distinct shift in the microbial community following the diet transition. Diet change reduced (p < 0.05) the abundances of short-chain fatty acid (SCFA)-producing bacteria and increased (p < 0.05) the relative abundance of potentially pathogenic bacteria, resulting in an elevated (p < 0.05) dysbiosis index. B. subtilis supplementation did not attenuate the microbial shifts caused by the diet transition. These findings confirm that an abrupt diet change significantly impacts some stool characteristics and fecal microbiota populations of dogs. Further investigation of Bacillus spp. strains and dosages is required to determine the potential benefits that they may provide during dietary transition.